Frameworks and measures for HIV‐related internalized stigma, stigma and discrimination in healthcare and in laws and policies: a systematic review. (12th July 2022) - Ferguson, Laura; Gruskin, Sofia; Bolshakova, Maria; Yagyu, Sachi; Fu, Ning; Cabrera, Nicky; Rozelle, Mary; Kasoka, Kasoka; Oraro‐Lawrence, Tessa; Stackpool‐Moore, Lucy; Motala, Aneesa; Hempel, Susanne
Abstract: Introduction: There is strong global commitment to eliminate HIV‐related stigma, and work in this area continues to evolve. Wide variation exists in frameworks and measures used. Methods: Building on the existing knowledge syntheses, we carried out a systematic review to identify frameworks and measures aiming to understand or assess internalized stigma, stigma and discrimination in healthcare, and in law and policy. The review addressed two questions: Which conceptual frameworks have been proposed to assess internalized stigma, stigma and discrimination experienced in healthcare settings, and stigma and discrimination entrenched in national laws and policies? Which measures of these different types of stigma and discrimination have been proposed and what are their descriptive properties? Searches, completed on 6 May 2021, cover publications from 2008 onwards. The review is registered in PROSPERO (CRD42021249348), the protocol incorporated stakeholder input, and the data are available in the Systematic Review Data Repository. Results and discussion: Sixty‐nine frameworks and 50 measures met the inclusion criteria. Critical appraisal figures and detailed evidence tables summarize these resources. We established a compendium of frameworks and a catalogue of measures of HIV‐related stigma and discrimination. Seventeen frameworks and 10 measures addressed at least two of our focus domains, with least attention to stigma and discrimination in law and policy. The lack of common definitions and variability in scope and structure of HIV‐related frameworks and measures creates challenges in understanding what is being addressed and measured, both in relation to stigma and efforts to mitigate or reduce its harmful effects. Having comparable data is essential for tracking change over time within and between interventions. Conclusions: This systematic review provides an evidence base of current understandings of HIV‐related stigma and discrimination and how further conceptual clarification and increased adaptation of existing tools might help overcome challenges across the HIV care continuum. With people living with HIV at the centre, experts from different stakeholder groups could usefully collaborate to guide a more streamlined approach for the field. This can help to achieve global targets and understand, measure and help mitigate the impact of different types of HIV‐related stigma on people's health and quality of life.